Active power reserve for frequency control provided by distributed generators in distribution networks - Rueda-Medina, Augusto C. [UNESP]; Padilha-Feltrin, Antonio [UNESP]; Mantovani, J. R.S. [UNESP] (Institute of Electrical and Electronics Engineers (IEEE), 2014)
In a smart grid environment, attention should be paid not only to the power supplied to satisfy loads and system losses but also to the services necessary to provide security and stability to the system: the so-called ancillary services. As they are well known the benefits that distributed generation can bring to electrical systems and to the environment, in this work the possibility that active power reserve for frequency control could be provided by distributed generators (DGs) in an efficient and economical way is explored. The proposed methodology was tested using the IEEE 34-bus distribution test system. The results show improvements in the capacity of the system for this ancillary service and decrease in system losses and payments of the distribution system operator to the DGs.
Keywords: active power reserver for frequency control; Distributed generators; distribution networks